(untitled) (Bangladesh Heart Journal, 2018)
Background: Atrial Fibrillation (AF) is common in early recovery period after cardio-thoracic surgery. There have been several pharmacological and nonpharmacological strategies suggested for prevention against AF after coronary artery bypass grafting. The purpose of this study was to evaluate the effect of oral amiodarone in the prevention of atrial fibrillation in patients who underwent off pump coronary artery bypass graft (OPCAB). Methods: This interventional study was conducted from February 2017 to January 2018 in the department of cardiac surgery, National Institute of Cardiovascular Disease (NICVD) Dhaka, Bangladesh. By purposive sampling a total of 100 patients having sinus rhythm who will undergo OPCAB were selected for the study. Among them 50 patients (Group-A) got amiodarone (600mg/day started 3 days prior to surgery) and 50 patients (Group-B) did not get amiodarone. Two (2) patients of group-A were excluded from the study due to conversion to on pump from off pump during operation. So, finally group A had 48 patients and group- B had 50 patients. Preoperative electrocardiography (ECG), serum electrolytes (e.g. potassium & magnesium), thyroid function test, liver function test and echocardiogram were done in all patients under study. Per-operative occurrence of AF was assessed on operation theatre monitor. Each patient was evaluated by continuous ECG up to 5th post-operative day (POD). Serum potassium & magnesium were measured in every alternative day up to 5th POD. ECG with long lead tracing was done for all patients on the day of hospital discharge & was recorded. Data were analyzed by SPSS 24.0 (Statistical Package for the Social Sciences) and tested by student T-test and Chi-square test. P < 0.05 was considered significant. Results: Pre-operative baseline characteristics were similar in both groups. Per-operative and postoperative AF occurred more frequently in group B than group A. Those were 10(20.83%) and 32(64.0%) peroperative, 9(18.75%) and 31(36.0%) immediate postoperative period respectively in group A and group B. The result was statistically significant (P value<.05). Post-operative amiodarone used in all patients who developed AF irrespective of groups. This also decreased AF significantly. There were statistically no significant difference found in postoperative serum electrolytes and use of inotropes, anti-arrhythmic drugs. All patients recovered well. Conclusion: This study concluded that preoperative oral administration of amiodarone can prevent the occurrence of atrial fibrillation in patients undergone Off Pump Coronary Artery Bypass (OPCAB). Bangladesh Heart Journal 2018; 33(1) : 67-73